2018
DOI: 10.1002/wene.296
|View full text |Cite
|
Sign up to set email alerts
|

Towards a fully integrated North Sea offshore grid: An engineering‐economic assessment of a power link island

Abstract: An increasing share of variable power feed‐in is expected in the next decades in the European power system, with a particularly high offshore wind potential in the North Sea region. This demands more temporal‐ and spatial flexibility in the system, an adequate grid infrastructure can provide both. This study presents an engineering‐economic approach evaluating the impact of novel infrastructure designs towards a fully integrated North Sea offshore grid, including TenneT’s vision of a power link island (PLI). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
(37 reference statements)
0
7
0
1
Order By: Relevance
“…The literature also discussed the need for policy support to enable market entry for green H2 and scale up the H2 value chain for further cost reductions [11,12,14,29,37,53,62,63,65,[67][68][69][70][71][72][73][74][75][76][77]. The literature review indicated that green H2 costs are expected to continue decreasing as renewable energy costs decrease and economies of scale are achieved.…”
Section: Primarily Cost Focused Benchmarking: Conventional Feasibilit...mentioning
confidence: 99%
See 1 more Smart Citation
“…The literature also discussed the need for policy support to enable market entry for green H2 and scale up the H2 value chain for further cost reductions [11,12,14,29,37,53,62,63,65,[67][68][69][70][71][72][73][74][75][76][77]. The literature review indicated that green H2 costs are expected to continue decreasing as renewable energy costs decrease and economies of scale are achieved.…”
Section: Primarily Cost Focused Benchmarking: Conventional Feasibilit...mentioning
confidence: 99%
“…The assessments considered factors like location, types of RES, and infrastructure and often included different H2 production pathways. The most common pathway was the offshore platform with a centrally placed electrolyzer [8,13,20,22,29,42,44,63,72,76,[83][84][85][86][87][88][89][90][91]. Figure 3 illustrates three different H2 concepts: shoreline, platform, in-turbine.…”
Section: Business Case Driven Approach: Innovation and Commercial Per...mentioning
confidence: 99%
“…One likely solution is the idea of an artificial island, which is being discussed among the countries surrounding the North Sea, which can act as an energy hub for all countries of the region and named ‘North Sea Wind Power Hub’ …”
Section: Infrastructural Requirements For Offshore Sng Productionmentioning
confidence: 99%
“…One likely solution is the idea of an artificial island, which is being discussed among the countries surrounding the North Sea, which can act as an energy hub for all countries of the region and named 'North Sea Wind Power Hub' . 36 The vision is based on the idea of building an artificial island at a central location with good potential for wind, depicted in Fig. 11.…”
Section: Infrastructural Requirements For Offshore Sng Productionmentioning
confidence: 99%
“…4 期 高丽萍 等:海上深水区风电场并网的空间布局优化 等 [8] 通过 Balmorel 模型对包含风电的欧洲北海电网进行了线路优化,结果表明汇集输电比 直接并网具有更好的经济性能;Chen 等 [9] 选择了三种不同的拓扑结构进行优化,结果说 明有枢纽岛的输电方案不仅总成本最低,在电力供应的安全性上也优于其他方案。在评 估比较方面,研究对象以固定规模的风电场为主,Houghton 等 [10] 对两种风电场输电方案 进行了成本效益分析,结果表明 h 型并网结构具有较好的运行效益;Kristiansen 等 [11] 和 Traber 等 [12] 以欧洲北海海上风电为研究对象,分别设置了 3、4 种情景来比较风电汇集送 出和直接并网的差异,结论均包括海上风电汇集送出有更好的经济效益。对于风电并网 后的电力消费,Li 等 [13] 建立了一个基于可再生能源消费的优化模型,模型结果表明能够 通过需求侧调整,从而促进可再生能源的消纳;帅挽澜等 [14] 提出了一种"源-网-荷-储"协同优化运行方法,结果表明,所提方法能够有效提升风电消纳空间。但是,目前 在海上风电送出的空间布局研究上,优化设计方面的研究侧重点并非风电场,评估比较 方面的研究对象虽为风电场,但忽略了优化设计的重要性;另外,现有研究仅为二维平 面计算,精度有待提高。 本文借鉴北海海上风电枢纽计划 (NSWPH) 提出的枢纽岛设想 [15] ,将风电汇集至岛 屿再送至陆地,研究深水区风电场并网的空间布局优化方法,分析深水区风电场并网空 间布局的特点及其影响因素。聚焦海上风电送出空间布局的优化设计研究,以固定规模 的风电场为研究对象,将海底地形因素转化为投资成本,以总投资成本最小化为目标函 数,建立了深水区风电场并网的三维空间布局优化设计模型,并以粤东地区为例进行分 析。本文在前人研究的基础上,开发了针对于海上风电送出空间布局的优化方法,实现 了三维空间计算,计算精度提高。 1 研究方法与数据来源 1.1 研究区概况 数据表明,广东省土地利用中存在浪费 [16] ,而根据 《广东省海上风电发展规划 (2017-2030 年)(修编)》 [17] ,粤东深水区风电场址二~六号的规划装机容量达 47.7 GW…”
unclassified